Immigration policy and self-selecting migrants - Milo Bianchi (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
We explore the implications of migrants' self-selection for the determination of immigration policy in a simple model where incentives and resources to migrate vary with skills. We show how self-selection determines the response of potential migrants to immigration policy changes, which is crucial for predicting the effects of such policy in the receiving country. For example, restricting immigration when it is low skilled may worsen self-selection and thus the receiving country skill distribution. These selection effects may lead low skilled natives to support a more restrictive policy even though current immigrants are not harmful for them, and the receiving country government to impose significant restrictions even in a purely utilitarian world.
Keywords: D78; F22; J61; O24; 330; Immigrant self-selection; immigration policy preferences; political economy of immigration; Public Choice; Internationale Wanderung; Einwanderung; Migrationspolitik; Theorie; Welt